(untitled) (Leuven, Belgium,Leuven, Belgium, 1992)
The irrigation indices relative water supply (RWS) and cumulative relative water supply (CRWS) were used. The weekly water balance were used to compute these irrigation indices using the recommended irrigation supply given by scheduling program at secondary off-takes regulated by constant head orifices (CHOs) and feedback data at the field level.
Keywords: Water management,Quản lý nước,Irrigation,Tưới nước; Management,Quản lý